Health Information Systems - Bréant, C.; Section Editor for the IMIA Yearbook Section on Health Information Systems (Yearbook of Medical Informatics, 2010)
Objectives: Summarize excellent current research in the field of Health Information Systems.Method: Synopsis of the articles selected for the IMIA Yearbook 2010.Results: Five papers from international peer reviewed journals have been selected for the section on health information systems.Conclusions: The elected articles illustrate how health care IT alignment, assessment and benchmarking have become a challenge and a key aspect to the strengthening of health information systems in order to maintain and expand the objectives and strategies of organizations.
Keywords: Medical informatics; International Medical Informatics Association; health information systems; hospital information systems